Melanopsin-Mediated Acute Light Responses Measured in Winter and in Summer: Seasonal Variations in Adults with and without Cataracts - Münch, Mirjam; Ladaique, Myriam; Roemer, Ségolène; Hashemi, Kattayoon; Kawasaki, Aki (Frontiers in Neurology, 2017)
Seasonal adaptation is a ubiquitous behavior seen in many species on both global hemispheres and is conveyed by changing photoperiods. In humans this seasonal adaptation is less apparent, in part because changes in daylength are masked by the use of electrical lighting at night. On the other hand, cataracts which reduce light transmission, may compound seasonal changes related to the reduced daylength of winter. To better understand the effects of different photoperiod lengths in healthy adults without and with cataracts we tested their melanopsin-mediated light responses in summer vs. winter. Fifty-two participants (mean age 67.4 yrs; 30 with bilateral cataracts and 22 age-matched controls with clear lenses; pseudophakes) were tested twice once in summer and once in winter. At each test session we assessed the electroretinogram and pupil responses during daytime and we determined melatonin suppression, subjective sleepiness and mood in response to light exposure in the evening. Circadian rest-activity cycles and sleep from activity recordings were also analyzed for both seasons. Both groups had similar visual function. There were no seasonal differences in the electroretinogram. For the pupil responses to bright blue light, the post-illumination response (PIPR) was greater in winter than summer in pseudophakes, but not in cataract participants, whereas melatonin suppression to acute light exposure showed no differences between both groups and seasons. Overall, intra-daily variability of rest-activity was worse in winter but participants felt sleepier and reported worse mood at the laboratory in evening time in the summer. Those with cataracts had poorer sleep quality with lower sleep efficiency, and higher activity during sleep in winter than summer. In this study, the PIPR showed a seasonal variation in which a larger response was found during winter. This variation was only detected in participants with a clear intraocular lens. In the cataract group, visual function was not impaired yet these participants showed a lack of seasonal changes in the pupil response to blue light and poorer sleep in winter. These findings raise the question for tailored lighting conditions for cataract patients in order to counter potentially deleterious effects of living with chronically lower light exposure.